Brain Abnormalities in Different Phases of Working Memory in Schizophrenia: An Integrative Multi-Modal MRI Study. Issue 9 (September 2019) - Fan, Feng-Mei; Xiang, Hong; Wen, Yun; Zhao, Yan-Li; Zhu, Xiao-Lin; Wang, Yun-Hui; Yang, Fu-De; Tan, Yun-Long; Tan, Shu-Ping
Abstract : Abstract: The current study aimed to examine both gray matter and functional activity changes in schizophrenia by combing both structural and task-related functional magnetic resonance imaging (fMRI). Nineteen patients with schizophrenia and 17 controls were recruited. The fMRI scan was performed while performing a working memory (WM) task. In terms of task performance, accuracy did not differ between groups, but there were significant differences in reaction time. Compared with controls, patients exhibited decreased functional activation in prefrontal areas, insula, lingual gyrus, and superior temporal gyrus during different phases of WM. The subcallosal cortex showed increased activation. Intriguingly, a structural-functional correlation was found in the left dorsolateral prefrontal cortex, anterior cingulate cortex, and subcallosal cortex in patients when performing high - load WM task. This study demonstrated both impaired gray matter volume and functional activation during WM in schizophrenia, suggesting structural and functional impairments. The structural-functional correlation in schizophrenia suggested that structural damage in schizophrenia might induce a decreased ability to modulate functional response in accordance with increasing task difficulty.